The Evaluation of Spinning Chambers of Pneumo-mechanical Spinning Machines - Sherzod Korabayev; Orif Alimov; Guzal Jabborova (Genius Journals, 2022)
In the article analysed the corrosion of the rotors of pneumomechanical spinning machines in industrial conditions.
Keywords: spinning machine, rotor, chamber, decay